Knowledge, Attitude, and Practices (KAP) of Diabetics Towards Diabetes and Diabetic Retinopathy in Riyadh, Saudi Arabia: Cross-Sectional Study - Al-Yahya A (Dove Medical Press, 2020)
Abdulrahman Al-Yahya,1 Alwaleed Alsulaiman,1 Abdulrahman Almizel,1 Abdulrahman Barri,1 Fadwa Al Adel2 1College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2College of Medicine, Princess Nourah bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Fadwa Al Adel Email FFAladel@pnu.edu.saBackground: Diabetes mellitus (DM) and its complication present a major morbidity burden among Saudi population. Awareness and proper knowledge of this highly prevalent disease is crucial to enhance early detection and proper intervention. Therefore, the main aim of this study was to identify the knowledge, attitude, and practices (KAP) of diabetic patients towards diabetes and diabetic retinopathy in Riyadh, Saudi Arabia.Methods: This cross-sectional study was conducted in 50 randomly selected primary care centers and two university hospitals in Riyadh, Saudi Arabia, between May and December 2018. Diabetic patients ≥ 18 years old were enrolled in the study. A validated KAP-45 questionnaire was used to assess the KAP levels of diabetics towards diabetes and diabetic retinopathy.Results: A total of 313 participants were enrolled in the study. The majority were males 168 (59.8%). The median age was 49 ± 24, and the median duration of diabetes was 8 ± 11 years. The average knowledge score for diabetes was 10 (good). While the average knowledge score for diabetic retinopathy was 4.5 (suboptimal). The average attitude scores for both diabetes and diabetic retinopathy were 0 and 2 (suboptimal), respectively. The average practice score for diabetes was 5 (good) while it was 3 (low) for diabetic retinopathy. The most common barrier to comply with regular follow-up was inadequate knowledge about the importance of periodic eye exam 47.1% (107). Patients with low socio-economic status had a significantly poor knowledge regarding diabetes (P< 0.0001) and diabetic retinopathy (P< 0.015), respectively. However, patients with low educational level had a significantly poor knowledge (p< 0.0001) and poor practice regarding diabetes (P< 0.013), respectively.Conclusion: It is important to improve education and awareness of DM and diabetic retinopathy among diabetics, as it’s essential for controlling the disease and reducing its complications, by improving patient compliance to treatment and follow-up.Keywords: DM, diabetes mellitus, DR, diabetic retinopathy, regular eye exam, primary care, diabetes awareness, knowledge, attitude and practice